The Non-Democratic Roots of Elite Capture: Evidence From Soeharto Mayors in Indonesia - Martinez-Bravo, Monica; Mukherjee, Priya; Stegmann, Andreas (Econometrica, 2017)
Democracies widely differ in the extent to which powerful elites and interest groups retain influence over politics. While a large literature argues that elite capture is rooted in a country's history, our understanding of the determinants of elite persistence is limited. In this paper, we show that allowing old-regime agents to remain in office during democratic transitions is a key determinant of the extent of elite capture. We exploit quasi-random from Indonesia: Soeharto-regime mayors were allowed to finish their terms before being replaced by new leaders. Since mayors' political cycles were not synchronized, this event generated exogenous variation in how long old-regime mayors remained in their position during the democratic transition. Districts with longer exposure to old-regime mayors experience worse governance outcomes, higher elite persistence, and lower political competition in the medium run. The results suggest that slower transitions towards democracy allow the old-regime elites to capture democracy.